A research review of the religious and social services of the special (disabled) companions of the Prophet (peace and blessings of Allah be upon them): خصوصی(معذور) صحابہ کرام رضی اللہ عنہم کی دینی وسماجی خدمات کا تحقیقی جائزہ - Hussain, Bilawal; Uddin, Dr. Nasir; Imran, Dr. Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
The Almighty Allah has created a variety of creatures in the universe, and nothing has been created without purpose. Every creation has a definite reason behind it. Among all the creations, humans are granted superiority and made as Allah's vicegerents on earth. The world has been made a testing ground for humans, where some face trials through health and well-being, while others encounter tests in the form of illness and disabilities. In Islam, there is no room for inferiority or despair. The history of Islam is filled with examples of individuals with disabilities who, through their tireless efforts, made significant contributions to their religion and recorded their marks in the world of knowledge. Islam encourages both able-bodied and disabled individuals to rise above despair and advance, offering inspiration and hope, particularly to those facing physical challenges. The lives of the companions of Prophet are rich in contributions to Islam. Not only did the general companions of Prophet contribute to the propagation and welfare of Islam, but special (disabled) companions of Prophet, despite their physical challenges and various obstacles, played key roles in the fields of knowledge, society, and politics. Despite being granted certain exemptions for the disabled in Islamic teachings, these companions of Prophet chose to pursue determination and resilience. Their efforts continue to serve as a beacon of hope and inspiration for both the general and specially-abled individuals in contemporary times.